Comparative analysis of bile metabolic profile in patients with biliary obstruction complicated by Clonorchis sinensis infection - Zhang, Xueli; Han, Su; Jiang, Xu; Duan, Shanshan; Gao, Yannan; Ding, Jian; Li, Xiang; Sun, Beibei; Hu, Xinyi; Zhang, Xiaoli; Zhang, Weizhe (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Clonorchiasis is an important foodborne parasitic disease. However, eggs of C. sinensis cannot be detected in faeces during biliary obstruction. Moreover, many diseases can cause biliary obstruction, such as gallstones, adenocarcinoma, cholangiocarcinoma and Ascaris lumbricoides infection. Therefore, it is of great significance to distinguish between patients of biliary obstruction and biliary obstruction with C. sinensis infection.Methods: A total of 48 biliary obstruction patients were enrolled, including 23 infected with C. sinensis and 25 non-infected subjects. The bile samples were collected by Endoscopic Retrograde Cholangiopancretography and analyzed using UHPLC-QTOF-MS. Additionally, multivariate statistical analysis methods were employed to identify differential metabolites. Next, bile amino acids levels were determined by targeted metabolomics analysis.Result: A total of 146 and 132 significant metabolites were identified in ESI+ and ESI− modes, respectively. The levels of amino acids (asparagine, glutamate, ornithine), and polyamines (spermidine and spermine) were significantly changed.Targeted analysis showed that the levels of amino acids (such as L-arginine, L-glutamine, L-lysine, L-propionic, L-tyrosine et al.) were lower in OB+C.s compared to OB patients. Marked metabolic pathways were involved in "Glutathione metabolism", "Caffeine metabolism", "Alanine, aspartate and glutamate metabolism", "Arginine and proline metabolism", "Purine metabolism", "Beta-Alanine metabolism" and "D-glutamine and D-glutamate metabolism".These results show that there were significant difference between OB+C.s and OB patients, especially in amino acids. The metabolic signature and perturbations in metabolic pathways may help to better distinguish OB+C.s and OB patients.